Nourish: Promoting Body Acceptance through Christ-Centered Identity in Female Collegiate Cross Country Runners - Kirsten E Howland; Melinda B. Smith (Movement and Being: The Journal of the Christian Society for Kinesiology, Leisure and Sports Studies, 2024)
Competitive runners are at increased risk for developing eating disorders (EDs), which can have serious effects on both sport and life. Clinical and psychological treatments for EDs are largely ineffective; therefore, to reduce the incidence of disordered eating in young runners, there is a need for preventative programs focused on shifting cultural attitudes and mindset. The purpose of this study was to implement and evaluate Nourish, a Biblically-based pilot program designed to promote body appreciation and a holistic view of the self through rooting identity in Christ. Seven members of the women’s cross country team at a private Division III Christian institution completed the 9-week program pilot with an overall adherence rate of 54%. Participants rated the program as valuable, appreciated the time spent with teammates, and highly recommended Nourish to other runners. Despite the moderate adherence rate, evaluations and focus group feedback indicate that Nourish is a valuable asset to a cross country program, and with future research and refinement could have a greater impact on identity and body image.
Keywords: disordered eating; body appreciation; identity; runners